Research projects 1987-1991 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Research projects 1987-1991 Vol. 3 edited by S Risopoulos 1996 274pp ISBN 92 9081 151 X published by, and available from CTA to those mentioned above.